Edukasi Perawatan Kaki pada Penderita Diabetes Mellitus di Wilayah Kerja Puskesmas Syamtalira Aron - Ainil Yusra; Syahabuddin Syahabuddin; Marlina Marlina (Jurnal Health Sains, 2023)
A serious complication that is often found in people with Diabetes Mellitus (DM) is diabetic foot ulcers. One of the primary prevention efforts for complications of diabetes mellitus such as the risk of neuropathy and foot ulcers is to provide health education about foot care for people with diabetes mellitus to increase knowledge and skills in performing routine and independent foot care. The target of this community service program is people with diabetes mellitus in the working area of the Syamtalira Aron Health Center, Syamtalira Aron District, totaling 25 people. The problem encountered is that DM sufferers still lack information about how to properly and correctly treat diabetic feet. There is no health team that provides direct education to DM sufferers about diabetic foot care techniques. The method used in this activity is to provide education and simulation/practice of diabetic foot exercises using power point media and distributing leaflets about the management and care of feet in people with DM. After educational activities and foot care simulations were carried out on November 14 and 15 2022 there was an 80% increase in knowledge in the good category and after the foot exercise simulation/exercise there was an increase in skills in doing foot care, namely 96%. This shows the target achievement in accordance with the expected results. The output that is expected to be achieved from this activity is that this program can provide benefits to the community, especially the target audience, thereby increasing the quality of human resources and the results can be published nationally with the ISSN and e-ISSN.